2022
DOI: 10.1007/s11517-021-02490-z
|View full text |Cite|
|
Sign up to set email alerts
|

Development of a dedicated 3D printed myocardial perfusion phantom: proof-of-concept in dynamic SPECT

Abstract: We aim to facilitate phantom-based (ground truth) evaluation of dynamic, quantitative myocardial perfusion imaging (MPI) applications. Current MPI phantoms are static representations or lack clinical hard- and software evaluation capabilities. This proof-of-concept study demonstrates the design, realisation and testing of a dedicated cardiac flow phantom. The 3D printed phantom mimics flow through a left ventricular cavity (LVC) and three myocardial segments. In the accompanying fluid circuit, tap water is pum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…These initial results demonstrated that zeolite indeed provides a certain amount of [13N]ammonia trapping, which appears to be controllable by using different tissue mimicking material compositions ( Figure 4 and Figure 7 ). As a result, the phantom heart contours were well recognized by the software, as with previous SPECT measurements [ 16 , 26 ]. No activity can occur at the location of the partitions in the myocardial tissue volumes of the phantom.…”
Section: Discussionsupporting
confidence: 71%
“…These initial results demonstrated that zeolite indeed provides a certain amount of [13N]ammonia trapping, which appears to be controllable by using different tissue mimicking material compositions ( Figure 4 and Figure 7 ). As a result, the phantom heart contours were well recognized by the software, as with previous SPECT measurements [ 16 , 26 ]. No activity can occur at the location of the partitions in the myocardial tissue volumes of the phantom.…”
Section: Discussionsupporting
confidence: 71%
“…The phantom setup has emerged from the redesign of a previously described myocardial perfusion phantom [15]. Phantom redesign concerned a novel way of tissue simulation, integration of coronary branches in the phantom model and improved sealing to prevent leakage.…”
Section: Methodsmentioning
confidence: 99%
“…As a result, the phantom heart contours were well recognized by the software, as with previous SPECT measurements. 18,28 No activity can occur at the location of the partitions in the myocardial tissue volumes of the phantom. We have used these markings in the polar maps to facilitate standardized orientation and evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, in recent decades, a shift towards dynamic imaging, hybrid imaging (for attenuation correction) and towards other imaging modalities is ongoing. 28,29 For example, magnetic resonance imaging (MRI) has become a common MPI method and possibilities with ultrasound (US) and computed tomography (CT) are being explored as well. Noteworthy is that current clinical implementation of these multimodal MPI procedures varies widely.…”
Section: Innovation In Myocardial Perfusion Imagingmentioning
confidence: 99%
See 1 more Smart Citation